Respuesta :
Answer: 6) x₁ = 4 and 3) x₂ = -3/2
Step-by-step explanation:
First we rearrange the terms:
4x²-7x = 3x + 24
4x²-7x -3x -24 = 0
4x²-11x -24 = 0
This is a quadratic equation having the form ax² + bx + c = 0
We can solve it by applying the formula:
[tex]x=\frac{-b+-\sqrt{b^{2}-4*a*c}}{2a} \\x=\frac{10+-\sqrt{10^{2}+4*4*24}}{2*4} \\x=\frac{10+-\sqrt{100+384}}{8} \\x=\frac{10+-\sqrt{484}}{8} \\x=\frac{10+-22}{8} \\x1=\frac{10+22}{8} \\x2=\frac{10-22}{8} \\[/tex]
x₁ = (10+22)/8 = 32/8 = 4
x₂ = (10-22)/8 = -12/8 = -3/2
Answer: 6) x₁ = 4 and 3) x₂ = -3/2